Diverse histomorphology of HER2‐positive breast carcinomas based on differential ER expression. Issue 4 (3rd February 2020) - Akashi, Momoko; Yamaguchi, Rin; Kusano, Hironori; Obara, Hitoshi; Yamaguchi, Miki; Toh, Uhi; Akiba, Jun; Kakuma, Tatsuyuki; Tanaka, Maki; Akagi, Yoshito; Yano, Hirohisa
Abstract : Aims: HER2‐positive (HER2+) breast carcinoma (BC) cases are often treated similarly; however, they can be classified as either luminal B (LH) or non‐luminal type (NLH) BC, which have different prognoses. In this study, we investigated the clinicohistomorphological features of each HER2+ BC subgroup. Methods and results: We classified 166 patients with HER2+ invasive BC into LH ( n  = 110, 66.3%) and NLH groups ( n  = 56, 33.7%). We further subclassified LH into patients with carcinomas expressing high levels of hormone receptors [LH‐high; Allred score, oestrogen receptor (ER) and/or progesterone receptor (PgR) 4–8, n  = 89, 53.6%] or low levels (LH‐low; Allred score, ER and/or PgR 2 or 3, n  = 21, 12.7%) for clinicohistomorphological characterisation. Morphological review showed that NLH included a percentage of patients with comedo necrosis, while LH patients had significantly more central scarring. In terms of immune responsiveness, NLH showed significantly higher rates of tumour‐infiltrating lymphocytes and healing. The LH‐high and NLH groups showed distinct characteristics (by both models, P  < 0.05) and the LH‐low group appeared to demonstrate intermediate characteristics according to multinomial analyses using covariates reflecting tumour morphology and immune response outcomes. Conclusions: These results support the classification of HER2+ BC into two major subgroups, LH‐high and NLH, based on tumour morphology and immune response; LH‐high proliferates via scirrhous and/or spiculated growth with a central scar, while the primary proliferation pattern of NLH is based on in‐situ carcinomas containing comedo necrosis with noticeable TILs and healing.